(untitled) (Research, Society and Development, 2021)
The fungi of the phylum Basidiomycota and the class Agaricomycetes have been known since the beginning of human history. Pleurotus ostreatus (Jacq.) P. Kumm, a florida variety, belongs to the Pleurotaceae family, and has a high capacity to degrade compounds based on lignin and cellulose. Due to this, the production of edible mushrooms presents an important alternative for the bioconversion of agro-industrial residues into food biomass. In this sense, the study aimed to produce edible mushrooms Pleurotus ostreatus, a florida variety, adding commercial value to agro-industrial and wood residues obtained in the northern region of the state of Mato Grosso, in addition to investigating the biological efficiency and measuring the loss of organic matter from the substrates. The substrates used were sawdust, cupuaçu leaves and the aboveground part of cassava, arranged in 10 treatments, with 16 samples each, divided into four replications. Different combinations of substrates were defined for each treatment, containing a total of 600g for each sample. The data obtained referring to production were submitted to analysis of variance containing the coefficient of variation, the mean square of the residue and the value of the F test of Snedecor significant at 1%. The variables evaluated were total production, individual production, biological efficiency and loss of organic matter. The substrate composed of pure cassava vines or added with sawdust and/or cupuaçu leaves was the most suitable for the production of the edible mushroom Pleurotus ostreatus, variety florida. Pure sawdust is not recommended for cultivation.